Hydrothermal Vent Complexes Control Seepage and Hydrocarbon Release on the Overriding Plate of the Tyrrhenian-Ionian Subduction System (Paola Basin) - Rovere, Marzia; Mercorella, Alessandra; Gamberi, Fabiano; Zgur, Fabrizio (Frontiers in Earth Science, 2022)
Active seeps have been described in a wide range of geological environments and geodynamic contexts, which include continental shelves of non-volcanic passive margins and accretionary wedges. Fluids seeping in hybrid volcanic-sedimentary basins, characterized by the presence of magmatic intrusive complexes, have always received less attention. We detected and imaged dozens of distinct gas flares, as high as 700 m, on the continental slope of the Paola Basin in the southeastern Tyrrhenian Sea, at 550850 m water depth. The sedimentary basin is surrounded by Pleistocene active and inactive volcanoes and volcanic-intrusive complexes, which formed in the back-arc basin of the Calabrian subduction zone, in response to subduction-induced mantle flow. Gas flares develop above pockmarks, craters and mud flows that form over and along the scarps of mound structures and correspond to seismic zones of free gas accumulation in the sub-seafloor. Here, authigenic siderite, showing enrichment in d13C and d18O likely related to methanogenesis and intermittent venting of deep-sourced CO2, precipitate. Multichannel seismic reflection data showed that the gas flares develop in correspondence of doming and diapirism apparently originating from the top of the Messinian evaporites and nearby magmatic sills, that are present in the lower part of the Plio-Quaternary succession. These diapiric structures can be related to hydrothermal vent complexes fed by the igneous intrusions. Our data suggest that the vent complexes acted as fluid migration pathways and gas conduits, which at times are bounded by deep-rooted normal faults, leading to post-explosive near-surface microbial activity and seep carbonate formation. Fluids being mobilised by magmatism in the study area include: hydrocarbons and hydrothermal fluids generated at depth, interstitial water expelled during formation of polygonal faults. The close spatial correlation between seafloor seep manifestations, fluid migration pathways in the sub-surface involving part of the Messinian units and igneous features indicates that magmatic activity has been the main driver of fluid flow and can have a long-term effect in the southern Tyrrhenian Sea.